The economic impacts of the 2018 Winter Olympics. Issue 7 (November 2021) - Wood, Jeremy; Meng, Samuel
The economic viability of the 2018 Pyeongchang Winter Olympics is still being debated. Using the latest available input–output tables and tourism data, this study estimates the short-run impact of the event. The estimated macroeconomic effect shows that tourism spending linked to the 2018 Winter Olympic Games has contributed ₩1.9 trillion to national output, which is greater than the operational cost of ₩1.7 trillion. It is estimated that the ₩11.5 trillion of infrastructural investment may have induced ₩18.5 trillion of gross domestic product for the national economy, so hosting the 2018 Winter Olympic Games is beneficial to South Korea. The sectoral effect shows that the increase in tourism demand benefits not only tourism sectors but also non-tourism sectors due to significant indirect and induced effects.